Hubungan kejadian asfiksia neonatorum dengan perkembangan anak usia 6 – 24 bulan di RSUD Luwuk Kabupaten Banggai Sulawesi Tengah - Inaya Dg Taha; Elizabeth Herini; Djauhar Ismail (Fakultas Kedokteran Universitas Gadjah Mada, 2017)
Neonatal asphyxia and growth development of children aged 6-24 months in Luwuk hospital, Central SulawesiPurposeThis research aimed to explore the associations between the occurrences of asphyxia neonatorum and development of children at the age of 6-24 months at hospital of Luwuk, South Sulawesi.MethodsA quantitative approach was employed to gather the data for the study, utilizing a cross-sectional survey design. The sample (n = 6-24 months) consisted of children at hospital of Luwuk of Banggai, South Sulawesi. The research instrument to collect development data of the infants was DDST II. Bivariate analysis was conducted by using chi-square tests to investigate any strong association between independent variable and dependent variable using Ratio Prevalence. Multivariate analysis was conducted by using logistic regression tests using a 95% Confidence Interval and a significance level of 0.05.ResultsThe occurrence of asphyxia neonatorum was statistically significant with the development of children at the age of 6-24 months (p<0.005). Children who experience asphyxia neonatorum were more likely with greater risk 2.11 times to have suspect development than those who did not.ConclusionThere was an association between the occurrences of asphyxia neonatorum and the development of children at the age 6-24 months at hospital of Luwuk of Banggai, South Sulawesi.